(untitled) (International Journal of Emerging Trends in Science and Technology, 2017)
The objective of physical laboratory training is to provide an experimental base for the theoretical concepts introduced during the lectures. It gives an opportunity to students to verify ideas which they learn in theory classes. Practical ability to perform experiments, record and analyze data is usually acquired through practice. Practice is essential to being able to make the connection between theory and experiment. E-learning platform creates the environment which is useful in achieving such connectivity. Present work emphasizes on need of implementation of Virtual experimental sessions as a model of Elearning to provide interactive multimedia contents to the students to higher their interests in understanding 3D physical world with computer models of real systems.